2019
DOI: 10.1186/s12933-019-0826-0
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and insulin resistance are related to restenosis and overall new PCI in subjects with normal glucose tolerance: the prospective AIRE Study

Abstract: Background In patients with Normal Glucose Tolerance (NGT) some causes of ischemic heart disease (IHD) were not completely investigated. The role both of metabolic milieu and adipokines in IHD progression was not fully investigated. Our aim was to assess the link between adipokines plasma levels, insulin resistance (IR) and IHD in NGT patients undergoing Percutaneous Coronary Intervention (PCI). Methods AIRE is a single-center prospective long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 47 publications
3
70
1
1
Order By: Relevance
“…As adiponectin is a clinically relevant biomarker, with previous studies showing that high levels of circulating adiponectin correspond to lower cardiometabolic risk [63,64]. Recently adiponectin has further been shown to correlate with the development of ischemic heart disease in normal glucose tolerance patients [65]. The findings presented in this study represent a possible novel mechanism for why higher levels of adiponectin are protective against the development and progression of metabolic diseases.…”
Section: Resultssupporting
confidence: 52%
“…As adiponectin is a clinically relevant biomarker, with previous studies showing that high levels of circulating adiponectin correspond to lower cardiometabolic risk [63,64]. Recently adiponectin has further been shown to correlate with the development of ischemic heart disease in normal glucose tolerance patients [65]. The findings presented in this study represent a possible novel mechanism for why higher levels of adiponectin are protective against the development and progression of metabolic diseases.…”
Section: Resultssupporting
confidence: 52%
“…A meta-analysis showed that increased plasma levels of adiponectin related to a high risk of mortality in subjects with CVD [ 40 ], while another study reported that high plasma adiponectin levels at discharge were associated with all-cause mortality during the 11.6 years follow-up in patients with acute myocardial infarction [ 41 ]. Sasso et al [ 42 ] showed that adiponectin played a role in progression of any stage of ischemic heart disease also in normal glucose tolerance subjects. However, Zoccali et al [ 43 ] found that high plasma adiponectin levels related to a low risk of cardiovascular outcomes in patients with end-stage renal disease, suggesting this protein was as a protective cytokine for the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to microvascular dysfunction, thrombus burden, unstable plaque, and diffuse distribution of atherosclerotic lesions, DM patients with ACS generally had higher incidences of LST/VLST and ISR [5,6]. In ammation and accumulation of reactive oxygen species and metabolic cytokines are primary mechanisms of vascular remodeling and progression of adverse myocardial diseases resulting from glycemic variability and hyperglycemia [7][8][9][10][11]. Furthermore, a previous study has reported that insulin resistance is higher in patients with cardiovascular disease [12].…”
Section: Dm and Dnlmentioning
confidence: 99%